2022
DOI: 10.1002/adfm.202113038
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Production of Acoustically Patterned Cells Within Hydrogel Fibers for Musculoskeletal Tissue Engineering

Abstract: Many mammalian tissues have a specific cellular arrangement that enables their unique function. For example, parallel alignment of myofibers enables uniaxial muscle contraction. To engineer structured tissues ex vivo, it is critical to recapitulate this cellular arrangement. Conventional 3D encapsulation often fails to recapitulate this complexity, motivating the need for advanced patterning approaches. In this work, an acoustofluidic device to continuously pattern mammalian cells within hydrogel fibers is eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The continuous and rapid formation of tissue structures such as cellular spheroids, linearly aligned cells within hydrogel fibers, and novel holographic patterning lays the groundwork for recapitulating complex tissue architectures to advance regenerative medicine. 93,103,275 Another possibility that MEMS-based acoustic devices offer, owing to the biocompatible and flexible materials, is to either be implanted inside the body or as wearable devices to deliver continuous, low-amplitude, localized and highfrequency acoustic waves with minimal energy decay. The integration of MEMS devices with electronic devices is also another potential area for acoustic devices where the implanted devices can be combined with wireless activation, charging, sensing, and continuous monitoring.…”
Section: Future Trend and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous and rapid formation of tissue structures such as cellular spheroids, linearly aligned cells within hydrogel fibers, and novel holographic patterning lays the groundwork for recapitulating complex tissue architectures to advance regenerative medicine. 93,103,275 Another possibility that MEMS-based acoustic devices offer, owing to the biocompatible and flexible materials, is to either be implanted inside the body or as wearable devices to deliver continuous, low-amplitude, localized and highfrequency acoustic waves with minimal energy decay. The integration of MEMS devices with electronic devices is also another potential area for acoustic devices where the implanted devices can be combined with wireless activation, charging, sensing, and continuous monitoring.…”
Section: Future Trend and Outlookmentioning
confidence: 99%
“…The continuous and rapid formation of tissue structures such as cellular spheroids, linearly aligned cells within hydrogel fibers, and novel holographic patterning lays the groundwork for recapitulating complex tissue architectures to advance regenerative medicine. 93,103,275…”
Section: Future Trend and Outlookmentioning
confidence: 99%
“…[135,[147][148][149] Especially, the combination of ultrasonic manipulation and 3D printing allows for precise control of material structure at both macro-and microlevels, [95,103] which offers potential applications in the field of tissue engineering and materials science. [152] Given the emerging capabilities of ultrasonic trapping technology described in this Review and the rapidly expanding requirements for microscale assembly, it is anticipated that ultrasound-based technology will help to drive the rapid growth in microfabrication processing over the coming years.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…More complex devices using sophisticated arrangements of transducers to form an array or acoustic holograms have been also developed and can be used to deposit different microscale objects in arbitrary 3D arrangements, which has considerable potential in materials science and tissue enginee ring. [38,100,112,131,[135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152] Through the construction of 1D or 2D multinodes acoustic field, SAW or BAW-based acoustic trapping devices can arrange multiple biological samples at the same time in well-defined 1D or 2D patterns, which enables high-throughput scree ning. [39,102,104,[118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] For instance, Tian et al showed that a periodic defect-free 2D microarray of coacervate microdroplets could be formed in an acoustic standing wave pressure field, which could be further functionalized by spontaneously sequestering dyes, enzymes, and particles.…”
Section: Potential Applications Of Micropatterning Technologymentioning
confidence: 99%
“…However, this assay typically gives rise to disorganized myotubes in the culture dish, rendering tissue engineering a highly desirable approach to produce aligned and functional skeletal muscle constructs [9][10][11] . Indeed, in past decades a multitude of studies reported on ordered architecture construction of skeletal muscle cells by using a variety of fabrication techniques including 3D printing 12 , micropatterning 13 , acoustic patterning 14,15 , magnetic actuation 16 , filamented light-beam biofabrication 17 and electrospinning 11,[18][19][20] . These efforts were harnessed to produce organized muscle constructs, however most often reported only on production of aligned myotubes in the absence of self-renewing muscle stem cells, thus limiting the study of myogenesis in biomimetic constructs 11,20 .…”
Section: Introductionmentioning
confidence: 99%